Preclinical Evaluation of the Nephroprotective Activity of Methanolic Leaf Extract of Bauhinia variegata L. in Gentamicin-Induced Nephrotoxicity in Wistar Albino Rats (Journal of Pharma Insights and Research, 2026)
Bauhinia variegata L. (Caesalpiniaceae), commonly known as Kanchanara or Mountain Ebony, is a medicinal plant used in traditional systems of medicine for several inflammatory and metabolic conditions [1-7]. Gentamicin is an effective aminoglycoside antibiotic, but its clinical use is limited by dose- and duration-dependent nephrotoxicity [18-20]. The present preclinical study evaluated the renal protective effect of methanolic leaf extract of Bauhinia variegata (MEBV) against gentamicin-induced nephrotoxicity in Wistar albino rats. Animals were divided into three groups: a normal group receiving distilled water, a toxic control group receiving gentamicin, and a test group receiving MEBV with gentamicin. At the end of the treatment period, serum creatinine, serum uric acid, blood urea nitrogen (BUN), urinary creatinine, urinary urea, urinary uric acid, and percentage change in body weight were assessed. Gentamicin markedly increased serum creatinine and BUN and produced weight loss, indicating renal injury. Co-administration of MEBV reduced these alterations and improved urinary biochemical parameters. These findings suggest that the methanolic leaf extract of Bauhinia variegata possesses significant nephroprotective activity, probably associated with antioxidant phytoconstituents such as flavonoids, tannins, and saponins [8-13].